Black middle class men's reactions and responses to unplanned pregnancy - Bujela, Khanyisile A. (My University, 2018)
Background: Unplanned pregnancy is a phenomenon that is commonly explored in South Africa. The male perspective is often neglected and overlooked when exploring unplanned pregnancy, hence most literature focuses on the female perspective. This neglect can result in gender bias where men are under and misrepresented by literature. The few studies that have attempted to speak directly to fathers explore unplanned pregnancy in two ways: explore the experiences of fathers in relation to how they were fathered and how this affects how they father their own children. The first study that was directed at exploring how young South African fathers experience unplanned pregnancy was only conducted in 2009 by Swartz and Bhana. This demonstrates that there is a dearth in research that focuses directly on young fathers in South Africa. The current study hoped to be a platform for the voices of Black men to be heard, for them to speak for themselves and not be spoken for or about, based on the experiences of women. Research aim and objectives: The aim of this study was to explore Black middle class men’s reactions and responses to unplanned pregnancy. The study’s objectives were as follows: To study how Black middle class men react to the news of an unplanned pregnancy. To study how Black middle class men respond to an unplanned pregnancy. To explore the reported factors which influence the manner in which Black middle class men respond to unplanned pregnancy. To explore how Black men from middle socio-economic backgrounds experience unplanned pregnancy. The research questions are: How do Black middle class men react to news of an unplanned pregnancy? What factors do Black middle class men perceive as influencing their responses to the unplanned pregnancy? What are the experiences of Black middle class men who have gone through an unplanned pregnancy? Research methods: An exploratory study was conducted using a qualitative approach from a social constructivist perspective. Nine men, around the Gauteng region (Johannesburg and Pretoria), were purposively sampled. Snowballing was used recruit the participants. These participants were recruited via social media platforms such as Facebook, Twitter. In the hopes to obtain the upper middle class, this study focused on men who have a stable monthly income and earn a minimum of R10 000. Semi-structured, one-on-one interviews were conducted in IsiXhosa, IsiZulu or English, depending on the participant’s preference, and were facilitated using a semi-structured interview guide. The interviews were audio recorded, transcribed and translated into English. Discourse analysis (Gee, 2011) was used to analyse the data. Findings: The findings of this study revealed discourses around the different circumstances; such as the nature of the participants’ relationship with the mother, participants’ upbringing, consideration of financial security, readiness and the individual’s awareness of their actions and the consequences thereof. There was evidence of blame shifting through discourses around falling victim of women’s deceit or manipulation as some of the participants perceived the pregnancy as the woman’s way of ‘trapping them into a happy-ever-after’. The findings suggest that news of the unintended pregnancy result in some psychological distress for some of the participants. This was reflected by discourses around feelings of disappointment, feeling that the experience was emotionally challenging for them to the extent that some expressed a need for social support throughout the experience. The influence of traditional constructions of masculinity and fatherhood was evident in some of the responses to the pregnancy. There was however evidence of a shift from these traditional constructions as reflected by discourses around fatherhood being associated with active participation in the child’s life. This study found that due to the lack of knowledge about the practice of intlawulo, a fine which the man pays to the woman’s family as a symbol of acceptance and acknowledgement of the paternity of the child (Langa & Smith, 2012), some of the participants reported that this practice was not significant to them. Religious discourses evidently influenced most of the participants’ opinions on termination of the pregnancy. Some participants reported having been punished by the church for impregnating someone out-of- wedlock. Discussion: This study intended to explore Black middle class men’s responses and reactions to unplanned pregnancy. It was observed in this study that a reaction to an unplanned pregnancy was understood in relation to the individual’s initial reaction to discovering the news of the pregnancy. This could take the form of shock, whilst a response was understood as the long-term response or actions taken at a later stage such as paying intlawulo. It was evident that social determinants surpassed scientific determinants when it comes to reactions and responses to unplanned pregnancy. This was reflected by the major discourse elicited in the findings which concerned the nature of participants’ relationship with the women whom they had allegedly impregnated. The nature of the relationship was understood as follows: The length of the relationship, the state and stability of the relationship (e.g. relationship in the process of ending/ a “Love-Back situation” and the intensity of the love felt for the partner. It was evident in this study that middle class men’s reactions and responses to unplanned pregnancy were informed by social determinants which were influenced by cultural and religious discourses that have been normalised leading to ambivalence to scientific determinants of unplanned pregnancy. Scientific determinants can be understood in relation to plausible biological processes responsible for conception and how (lack) knowledge of or ambivalence towards these processes influence reactions and responses to unplanned pregnancy. Recommendations: Programs and interventions that provide support to young Black fathers can help create good role models which could break the cycle of unpleasant experiences of being fathered. This could subsequently result in young Black men being motivated to become good fathers. Young Black men need to be challenged to critically engage with cultural discourses around women’s sexuality. Moreover, they need to be encouraged to take responsibility of their sexual behaviours. Increased involvement of young Black men in sexual and reproductive health education, dialogues and interventions could be an opportunity for them to gain more knowledge about their sexual behaviour and the consequences thereof. It is further recommended that young Black men be provided with more scientific knowledge around pregnancy. Conclusion: This study gave evidence that shows that young middle class Black men’s reactions and responses to unplanned pregnancy were informed by their personal experience of being fathered and cultural discourses around sexuality and courtship. Furthermore, social determinants of unplanned pregnancy were pivotal to the manner in which these participants constructed and experienced unplanned pregnancy. Relying on social determinants as opposed to scientific determinants is argued to be detrimental to paternal acknowledgement as this contributes to unplanned pregnancies which occur in less socially acceptable contexts being confronted with negativity. The knowledge generated by this study contributed to a knowledge gap on the reactions and responses of Black middle class men towards unplanned pregnancy.
A dissertation submitted in partial fulfillment of the requirements for the Master’s Degree in Community Based-Counselling Psychology in the Faculty of Humanities at the University of the Witwatersrand, 2018
Keywords: Fatherhood--South Africa; Middle class men--South Africa; Blacks--Family relationships--South Africa